2020
DOI: 10.3892/etm.2020.9410
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin modulates AMPK/SIRT1/NF‑κB signaling to inhibit inflammatory/oxidative stress responses in diabetic high fat diet‑induced atherosclerosis in the rat carotid artery

Abstract: Inflammation and oxidative stress serve interrelated roles in the development of atherosclerosis and other vascular diseases. Quercetin has been previously reported to exhibit numerous beneficial properties towards several metabolic conditions and cardiovascular disease. The present study aimed to evaluate the effects of quercetin on the 5'adenosine monophosphate-activated protein kinase (AMPK)/sirtuin 1 (SIRT1)/NF-κB signaling pathway and inflammatory/oxidative stress response in diabetic-induced atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…In detail, Zhang et al have observed that QE treatment in obese diabetic rats improves the lipid metabolism and reduces the number of atherosclerotic lesions, enhancing the activity of antioxidant enzymes in the carotid artery. They demonstrated, using a specific AMPK inhibitor (compound-C), that QE mitigates atherosclerotic damages, activating the AMPK/SIRT1/NF-κB signaling pathway [174].…”
Section: From Caloric Restriction To Cr-related Nutrients: Quercetinmentioning
confidence: 99%
“…In detail, Zhang et al have observed that QE treatment in obese diabetic rats improves the lipid metabolism and reduces the number of atherosclerotic lesions, enhancing the activity of antioxidant enzymes in the carotid artery. They demonstrated, using a specific AMPK inhibitor (compound-C), that QE mitigates atherosclerotic damages, activating the AMPK/SIRT1/NF-κB signaling pathway [174].…”
Section: From Caloric Restriction To Cr-related Nutrients: Quercetinmentioning
confidence: 99%
“…Among them, quercetin is a avonoid ingredient and exists widely in nature. Research showed that quercetin modulated AMPK/SIRT1/NF-κB signaling pathway [37] or JAK2/STAT3 pathway [38] to inhibit cell apoptosis and oxidative stress, reduce myocardial infarction size, improve ventricular remodeling and cardiac functionrelated biochemical indexes, and promote the recovery of cardiac blood ow. And a double-blind, placebocontrolled, randomized clinical trial demonstrated signi cantly elevated total antioxidant capacity [39].…”
Section: Analysis Of Active Ingredientsmentioning
confidence: 99%
“…Our results showed that high-dose 7S had negative effects on "cysteine and methionine metabolism, " "AMPK signaling pathway, " "galactose metabolism, " "starch and sucrose metabolism, " "ABC transporters, " and "amino sugar and nucleotide sugar metabolism" and a positive effect on "ferroptosis." Quercetin could inhibit oxidative stress and inflammatory responses by regulating the AMPK/SIRT1/NF-κB signaling pathway (Zhang et al, 2020), indicating that high-dose 7S might inhibit the absorption and utilization of carbohydrates in the feed of hybrid grouper, resulting in insufficient energy supply. Ferroptosis is caused by the accumulation of reactive oxygen radicals on membrane lipids because of the failure of glutathione peroxidase activity (Doll et al, 2016).…”
Section: Distal Intestinal Metabolomics In Response To 7s and Nabmentioning
confidence: 99%